Iatrogenic Tracheal Rupture after Endotracheal Intubation: A Case Report - Kraleva, Silvana; Trojikj, Tatjana; Talevski, Darko; Malefski, Dola; Bozinovska Beaka, Gordana (Lietuvos chirurgija, 2024)
Iatrogenic tracheal rupture is very rare condition and has a lot off causes (intubation, tracheostomy, bronchoscopy, esophagectomy), but orotracheal intubation is the most common. Diagnosis is based on the occurrence of symptoms that are not specific but highly suggestive: subcutaneous emphysema, respiratory insufficiency, pneumothorax, and hemoptysis. The appearance of subcutaneous emphysema as a first sign plays a main role for early diagnosis and rapid appropriate treatment. Diagnostic confirmation is possible by chest X-ray, thoracic computed tomography and bronchoscopy which confirmed the size and site of the lesion. Treatment can be conservative, in patients with small ruptures, less than 2 cm, and surgical in the majority of ruptures over 2 cm in length. Our case report presents an iatrogenic post-intubation tracheal rupture treated conservatively. Our patient was a 71-year-old woman, admitted in our hospital with fracture of right humerus for elective surgery. Her medical history was only arterial hypertension. She underwent general anesthesia, intubated with flexible ET tube, positioned in beach-chair position after introduction, and no complication occurred during surgery. 18 hours after surgery, after severe coughing, she suddenly developed subcutaneous emphysema of the facial, neck and upper anterior chest. Tracheal rupture was confirmed with a thoracic computed tomography and tracheobronchial fiber endoscopy. It showed a posterior tracheal transmural rupture 1 cm long, located 4 cm above the carina, covered with small tissue that opened in inspirium. Conservative treatment with antibiotic cover was performed, and the patient was discharged home in good condition, fourteen days after the initial injury.